Resistance characteristics of broad-leaf crop canopy in air-assisted spray field and their effects on droplet deposition - Wu, Shuo; Liu, Jizhan; Zhen, Junquan; Lei, Xiaojie; Chen, Yao (Frontiers in Plant Science, 2022)
Air-assisted spray technology is widely applied in high-efficiency pesticide applications. The resistance characteristics of the crop canopy reflect its energy dissipation effect on the assisted airflow, linking the structure of the crop canopy, the assisted airflow velocity, and the droplet deposition effect. Using a common broad-leaf crop canopy as its research object, this study investigated the resistance characteristics of the crop canopy in the air-assisted field on the basis of theoretical analysis and wind tunnel tests, discussing the feasibility of using the resistance characteristics of the crop canopy to evaluate its droplet deposition effect. The results showed that under the conditions of different leaf layers and initial leaf azimuth angles in the different layers, the canopy pressure drop exhibited a non-linear increasing trend with increases in the assisted airflow velocity, its regression function conforming to the Darcy–Forchheimer function configuration. Moreover, when the initial azimuth of single and multi-layer leaves was in the 90–270° range, the change rate of the canopy pressure drop with airflow velocity was within the 7–9 m/s range, there being a critical wind speed. However, with an increase in leaf layers in the crop canopy, the difference in the initial azimuth angle of the leaves and the corresponding change in the maximum canopy pressure drop and resistance coefficient were nonlinear, which could not be quantified as the result of the linear superposition of resistance characteristics of several single-layer leaves—that is, it should be regarded as a whole research object. Combined with the analysis of the influence of crop canopy resistance on droplet deposition, it is considered that when the crop canopy has multi-layered leaves in the airflow direction, the existing air-assisted spray technology can not guarantee the droplet deposition and canopy penetration at the same time.